Comparative Study Regarding Combating and Preventing Corruption in Romania and the Republic of Moldova - Weber, Iuliana (Acta Universitatis Danubius. Administratio, 2023)
The present paper wants to analyse the level of corruption in Romania and Moldova, the legal framework for civil liability, and the institutions responsible for preventing and combating corruption. Even if the respective countries differ in their form of government, international status, level of development, the fact that Romania is a member of UE, number of populations, and territory, it is known the fact that the Moldova legislation has changed in recent years, especially as concerning anti-corruption; many measures are inspired by Romanian and European legislation. Nobody has yet found a solution of guaranteed efficacy for the reduction and, ultimately, elimination of corruption in a society. With regards to the phenomenon of corruption, it is a truth accepted unanimously, according to which criminal prosecution, and disciplinary sanction against corrupted individuals can eliminate the offender, but cannot eradicate corruption. Consequently, corruption control can be implemented efficiently through society’s economic, political and moral recovery. Thus, we follow the similarities and differences between the two countries using a case study, and research at different international and regional organizations, to reach the conclusion referring to anticorruption measures and the way of civil liability in the two mentioned states.